Capsular thinning on magnetic resonance arthrography is associated with intra-operative hip joint laxity in women. Issue 2 (10th August 2020) - Packer, Jonathan D; Foster, Michael J; Riley, Geoffrey M; Stewart, Russell; Shibata, Kotaro R; Richardson, Michael L; Boutin, Robert D; Safran, Marc R
Abstract: Hip microinstability is a recognized cause of hip pain in young patients. Intra-operative evaluation is used to confirm the diagnosis, but limited data exist associating magnetic resonance arthrography (MRA) findings with hip microinstability. To determine if a difference exists in the thickness of the anterior joint capsule and/or the width of the anterior joint recess on MRA in hip arthroscopy patients with and without an intra-operative diagnosis of hip laxity. Sixty-two hip arthroscopy patients were included in the study. Two musculoskeletal radiologists blinded to surgical results reviewed the MRAs for two previously described findings: (i) anterior joint capsule thinning; (ii) widening of the anterior joint recess distal to the zona orbicularis. Operative reports were reviewed for the diagnosis of joint laxity. In all patients with and without intra-operative laxity, there were no significant differences with either MRA measurement. However, twenty-six of 27 patients with intra-operative laxity were women compared with 11 of 35 patients without laxity ( P  < 0.001). In subgroup analysis of women, the intra-operative laxity group had a higher rate of capsular thinning compared with the non-laxity group (85% versus 45%; P  = 0.01). A 82% of women with capsular thinning also had intra-operative laxity, compared with 40% without capsular thinning ( P  = 0.01). There were no differences regarding the width of the anterior joint recess. In this study, there was an association between capsular thinning and intra-operative laxity in female patients. Measuring anterior capsule thickness on a pre-operative MRA may be useful for the diagnosis of hip microinstability.